2017
DOI: 10.1007/s12008-017-0411-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical behavior of biocomposites using additive manufacturing

Abstract: Research on additive manufacturing (AM) has gained significant attention in recent years. In this study, two different matrices of polypropylene and polylactic acid materials filled with three different percentages of wood flour were employed; namely 10, 20, and 30%. Biocomposite filaments (developed by twin screw extrusion) were further used in AM by fused deposition modeling (FDM) to obtain testing samples for the characterization of the tensile and flexural properties through mechanical testing. Tensile and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 25 publications
1
17
0
4
Order By: Relevance
“…3D printing (3DP) or additive manufacturing is an emerging technology that enables the creation of innovative designs and the combination of materials that were previously impossible or impractical to make. The incorporation of fillers in 3DP has demonstrated that the filler's physical features could be transferred to the 3D printed object (Montalvo Navarrete et al, 2018; Zeidler et al, 2018). These attractive traits have been demonstrated with wood (Mirko et al, 2016; Tao et al, 2017), clays (Revelo and Colorado, 2018), metals (Gibson et al, 2018), and seashells (Graichen et al, 2017; Singamneni et al, 2018a; Zeidler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…3D printing (3DP) or additive manufacturing is an emerging technology that enables the creation of innovative designs and the combination of materials that were previously impossible or impractical to make. The incorporation of fillers in 3DP has demonstrated that the filler's physical features could be transferred to the 3D printed object (Montalvo Navarrete et al, 2018; Zeidler et al, 2018). These attractive traits have been demonstrated with wood (Mirko et al, 2016; Tao et al, 2017), clays (Revelo and Colorado, 2018), metals (Gibson et al, 2018), and seashells (Graichen et al, 2017; Singamneni et al, 2018a; Zeidler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thermal stability and safe zone of heating and processing of wood flour filled PLA or PP filament were investigated. Four zones, namely dehydration, a stable zone for FFF, slow decomposition, and rapid decomposition were well defined . Different degrees of thermal degradation temperature shifts were observed for cocoa shell waste PCL filaments with different lignocellulose contents from TGA analysis.…”
Section: Introductionmentioning
confidence: 91%
“…It could also enhance the understanding of materials and optimize the entire FFF 3D printing process for different applications. 23,25 The influences of nanocellulose contents (0, 1, 2.5, and 5 wt %) on thermal properties of nanocellulose filled PLA/PEG filament are shown in Figure 1(d). All the addition of nanocellulose increased thermal stability.…”
Section: Kinetic Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a great deals of attention and studies on the 3D printing of conventional and advanced materials, the number of studies on the AM of bio‐based reinforced composites is limited. [ 24 ] The fabrication of lightweight cellular structures with enhanced mechanical properties, which are 3D printed by fiber‐reinforced composite filaments, is the result of recent advances in AM technology [12f,25] . Producing architected cellular composites out of biological resources (i.e., bio‐based PLA) and waste materials (i.e., wood fibers) with enhanced multifunctional properties including stiffness and ultimate strength can be a turning point in sustainable design and fabrication of advanced materials.…”
Section: Introductionmentioning
confidence: 99%